Does the nomination scheme of the city manager matter for urban development policies? - Garmann, Sebastian (My University, 2014)
This paper examines the causal effect of a change in the nomination scheme of the city manager from appointment by the local council to election by the citizens on urban development policies. Using the fact that the timing of the reform was as good as random in municipalities of the German state Hesse, the author can utilize a difference-in-difference framework to estimate this causal effect. The author argues that when the city manager is elected by the voters, there is significantly less urban development than when the city manager is appointed by the municipal council.
Keywords: Verwaltung; Verwaltungsreform; Stadtentwicklung; Wahlen; Stadtverwaltung